Perbedaan Subjective Well Being dan Hardiness Pada Siswa SMA Program Akselerasi Dengan Program Reguler di Surakarta - Prasetya, Panji, Dr. Nanik Prihartanti, M.Si (2015)
This study aims to 1) determine whether there are differences in subjective well being and hardiness in students an accelerated program with regular program students, 2) to determine the level of SWB and Hardines on each program. Respondents in this study is a regular program students and students accelerated program. This research was conducted at SMA N 3 Surakarta. Sampling using cluster random sampling technique, namely the class scrambles to serve as research subjects. Students used as research respondents are regular class XII MIPA 1, MIPA 2 and class XII acceleration XI Aksel 1, XI aksel 3. Measuring instrument in this study a scale of Subjective Well Being and Hardiness scale. Calculation analysis of the data in this study using the t test (t-test), for the variables shown in subjective well being t = -1.301 with sig. (2-tailed) of (0.197) (p> 0.05), while in the variable indicated hardiness t = -0, 615 with sig. (2-tailed) of (0.348) (p> 0.05). The variable Mean Empirical subjective well being in regular classes (ME = 105.72) and the acceleration class (ME = 108.92). On Empirical Mean hardiness variables in regular classes (ME = 133.26) and the acceleration class (ME = 134.78). Show that there are differences but not significant subjective well being and hardiness in the regular program students and students accelerated program. Subjective well-being and hardiness acceleration and regular students in the category.